Cost effectiveness of treatment strategies for high risk prostate cancer. Issue 21 (7th September 2022) - Kowalchuk, Roman O.; Kim, Hayeon; Harmsen, William S.; Jeans, Elizabeth B.; Morris, Lindsay K.; Mullikin, Trey C.; Miller, Robert C.; Wong, William W.; Vargas, Carlos E.; Trifiletti, Daniel M.; Phillips, Ryan M.; Choo, C. R.; et al.
Abstract : Background: Patients with high‐risk prostate cancer (HRPC) have multiple accepted treatment options. Because there is no overall survival benefit of one option over another, appropriate treatment must consider patient life expectancy, quality of life, and cost. Methods: The authors compared quality‐adjusted life years (QALYs) and cost effectiveness among treatment options for HRPC using a Markov model with three treatment arms: (1) external‐beam radiotherapy (EBRT) delivered with 20 fractions, (2) EBRT with 23 fractions followed by low‐dose‐rate (LDR) brachytherapy boost, or (3) radical prostatectomy alone. An exploratory analysis considered a simultaneous integrated boost according to the FLAME trial (ClinicalTrials.gov identifier NCT01168479). Results: Treatment strategies were compared using the incremental cost‐effectiveness ratio (ICER). EBRT with LDR brachytherapy boost was a cost‐effective strategy (ICER, $20, 929 per QALY gained). These results were most sensitive to variations in the biochemical failure rate. However, the results still demonstrated cost effectiveness for the brachytherapy boost paradigm, regardless of any tested parameter ranges. Probabilistic sensitivity analysis demonstrated that EBRT with LDR brachytherapy was favored in 52% of 100, 000 Monte Carlo iterations. In an exploratory analysis, EBRT with a simultaneous integrated boost was also a cost‐effective strategy, resulting in an ICER of $62, 607 per QALY gained; however, it was not cost effective compared with EBRT plus LDR brachytherapy boost. Conclusions: EBRT with LDR brachytherapy boost may be a cost‐effective treatment strategy compared with EBRT alone and radical prostatectomy for HRPC, demonstrating high‐value care. The current analysis suggests that a reduction in biochemical failure alone can result in cost‐effective care, despite no change in overall survival. Abstract : External‐beam radiotherapy with low‐dose‐rate brachytherapy boost is a cost‐effective treatment strategy for high‐risk prostate cancer, demonstrating high‐value care. This analysis indicated that a reduction in biochemical failure alone can result in cost‐effective care, despite no change in overall survival.